Analisis Pengaruh Ketimpangan Gender Dalam Pendidikan, Kesehatan Dan Ketenagakerjaan Terhadap Produk Domestik Regional Bruto Di Provinsi Papua Barat Tahun 2015-2019 - Lubna Mustamir; Marcus R. Maspaitella; Danny Waimbo (JFRES Journal of Fiscal and Regional Economy Studies, 2022)
This study aims to analyze the effect of Gender Inequality in Education, Health, and Employment on the Gross Regional Domestic Product in West Papua Province 2015 – 2019. The type of this research is a quantitative method using secondary data where the data is obtained from the Indonesian Central Statistics Agency. The method of analysis in this study is panel data analysis (combined time series and cross-section) which is processed using the help of the Eviews9 program, and the regression model used is the Common Effect model. The results showed that the education and health variables had a positive and significant effect on GRDP, while employment had a positive but not significant effect on GRDP in West Papua Province. As well as for the simultaneous influence of the variable gender inequality in education, health, and employment on GRDP in West Papua Province.